Comparison of high tone therapy and transcutaneous electrical nerve stimulation therapy in chemotherapy-induced polyneuropathy. Issue 19 (May 2020) - Schaffler-Schaden, Dagmar; Sassmann, Robert; Johansson, Tim; Gampenrieder, Simon P.; Rinnerthaler, Gabriel; Lampl, Kathrin; Herfert, Juergen; Lenzhofer, Christiane; Landkammer, Yvonne T.; Rieder, Florian; Greil, Richard; Flamm, Maria; et al.
Abstract: Introduction: Chemotherapy-induced peripheral neuropathy (CIPN) is a worldwide concern in patients receiving neurotoxic agents for cancer therapy. High tone external muscle stimulation is a promising therapeutic approach to alleviate symptoms of CIPN. Methods: This pilot study aims to investigate whether the application of home-based high-tone external muscle stimulation therapy (HTEMS) improves symptoms of CIPN. The trial is planned as a therapist- and assessor-blinded, 1:1 randomized controlled study. A total of 50 patients with chemotherapy-induced peripheral polyneuropathy will be included. All patients will perform therapy at home. Study participants will be allocated randomly to the HTEMS therapy (intervention group) or to the transcutaneous electrical nerve stimulation (TENS, control group), respectively, following a standardized therapy schedule. Compliance of participants can be verified by reading out the tool box. Outcomes will be evaluated at baseline and after 8 weeks of home-based therapy. The primary outcome includes improvement of CIPN according to the patient-reported EORTC QLQ-CIPN 20 questionnaire. Secondary outcomes are the patient-reported change in health-related quality of life and clinician-reported changes of vibration sensibility, tendon reflexes, temperature sensibility, perception of touch, and strength of the lower leg muscles. Further a safety- and process evaluation will be performed. Discussion: This pilot RCT aims to evaluate the impact of home-based HTEMS as compared to TENS in CIPN. There is a need for an effective treatment for CIPN and the results of this study are expected to possibly identify a novel and effective treatment strategy in the future.